Changes in the Hemostasis System in Children with Hemorrhagic Vasculitis (Henoch-Schönlein purpura) (Texas Journal of Medical Science, 2023)
The article discusses changes in the hemostasis system in children with hemorrhagic vasculitis, in particular, damage to the walls of small vessels by immune complexes circulating in the circulatory system and activated components of the complement system, and then activation of all parts of the hemostasis system, as well as changes in the hemostasis system of blood vessels, platelets, plasma. Hemorrhagic vasculitis (IgAV) is classically a childhood disease with an incidence of about 10 cases per 100,000 a year. The pediatric form of this pathology is generally considered benign and self-limited. In contrast, IgAV in adults is less common but often associated with worse clinical course and outcome The results of studies conducted by different authors in different countries on the study of the processes of violation of the mechanisms of blood coagulation in hemorrhagic vasculitis in children are presented.